1984
DOI: 10.1111/j.1445-5994.1984.tb03780.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Hepatitis: Clinical Features, Diagnosis and Prognosis

Abstract: Nineteen episodes of ischemic hepatitis were diagnosed by hepatitic liver function tests and characteristic liver pathology in 17 patients. All patients had an acute illness associated with a likely fall in cardiac output although only five episodes were associated with documented hypotension. Right ventricular failure was severe in only four, mild in six, and absent in nine whilst left ventricular failure was clinically apparent in 16. The hepatitic illness was usually mild. No patient died as a direct result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 11 publications
4
65
1
1
Order By: Relevance
“…Defined as an 8-fold increase or greater in aspartate transaminase and alanine transaminase levels over normal or baseline values (18).…”
Section: Ischemic Hepatitismentioning
confidence: 99%
“…Defined as an 8-fold increase or greater in aspartate transaminase and alanine transaminase levels over normal or baseline values (18).…”
Section: Ischemic Hepatitismentioning
confidence: 99%
“…In HH originating from CHF, the onset is usually precipitated by one or more acute cardiac events, the most frequent being arrhythmia or pulmonary edema. [1][2][3][4] In the present study, such an event was observed in every episode of HH caused by CHF (control group 1). On the contrary, when HH was caused by an acute exacerbation of CRF, no precipitating factor could be elicited except for progressive deterioration of the respiratory status.…”
Section: Discussionmentioning
confidence: 82%
“…The review of published series including at least 4 cases of HH 1,2,4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] shows that exacerbation of CRF in patients free of left cardiac failure was the cause of HH in only 7 of 263 cases (2.6%). Moreover, clinical studies of asthmatic or CRF patients have reported normal or only slightly affected liver function tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations